2023
DOI: 10.3390/polym15051196
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Investigation of Poly(lactic acid) (PLA) Nanocomposites: Incorporation of Various Nanofillers and their Properties and Applications

Abstract: Poly(lactic acid) (PLA) is considered the most promising biobased substitute for fossil-derived polymers due to its compostability, biocompatibility, renewability, and good thermomechanical properties. However, PLA suffers from several shortcomings, such as low heat distortion temperature, thermal resistance, and rate of crystallization, whereas some other specific properties, i.e., flame retardancy, anti-UV, antibacterial or barrier properties, antistatic to conductive electrical characteristics, etc., are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 283 publications
0
20
0
Order By: Relevance
“…Furthermore, products from the thermal decomposition of GP such as protons (H + ) from the sugars could promote the break of ester bonds of PLA 37 . Thus, the formation of oligomers and acid lactic molecules through these two main ways could contribute to an autocatalytic degradation of the polymer 38 . Moreover, a possible poor dispersion of GP in the polymer matrix due to the immiscibility of the components could generate interfacial spaces where the heat flow transference was favored, resulting in a more aggressive thermal degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, products from the thermal decomposition of GP such as protons (H + ) from the sugars could promote the break of ester bonds of PLA 37 . Thus, the formation of oligomers and acid lactic molecules through these two main ways could contribute to an autocatalytic degradation of the polymer 38 . Moreover, a possible poor dispersion of GP in the polymer matrix due to the immiscibility of the components could generate interfacial spaces where the heat flow transference was favored, resulting in a more aggressive thermal degradation.…”
Section: Resultsmentioning
confidence: 99%
“…37 Thus, the formation of oligomers and acid lactic molecules through these two main ways could contribute to an autocatalytic degradation of the polymer. 38 Moreover, a possible poor dispersion of GP in the polymer matrix due to the immiscibility of the components could generate interfacial spaces where the heat flow transference was favored, resulting in a more aggressive thermal degradation. Finally, there was no evidence of changes on the thermal stability of PLA and biocomposite films when they were obtained at different extrusion temperatures.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Despite the promising properties of PLA, its exploitation in such applications is restricting due to certain shortcomings, some of which are its poor mechanical and barrier properties and its poor thermal stability. One effective way to overcome these restrictions and enhance its properties is the incorporation of nanoparticles in the polymer matrix 11,12 . As of today, there is a variety of nanomaterials that have been mixed with PLA to obtain bionanocomposite systems, both organic (cellulose nanocrystals, chitosan) and inorganic (graphene oxide, silica, Ag, etc) 13–17 .…”
Section: Introductionmentioning
confidence: 99%
“…One effective way to overcome these restrictions and enhance its properties is the incorporation of nanoparticles in the polymer matrix. 11,12 As of today, there is a variety of nanomaterials that have been mixed with PLA to obtain bionanocomposite systems, both organic (cellulose nanocrystals, chitosan) and inorganic (graphene oxide, silica, Ag, etc). [13][14][15][16][17] Among these nanoinclusions, titanium dioxide (TiO 2 ), an inert and low-cost inorganic nanomaterial, is a promising candidate for the production of bionanocomposites with improved physical properties compared to PLA.…”
mentioning
confidence: 99%
“…32 In vitro studies performed with PLA/nHAp revealed that cell adhesion and proliferation on the surface of the developed biocomposite support the biocompatible nature. 25,33 Thus, the PLA/nHAp biocomposite and membrane 34,35 is helpful in bone tissue repair.…”
Section: Introductionmentioning
confidence: 99%